2015
DOI: 10.1371/journal.pone.0128472
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of MicroRNA-124 Overexpression on Anti-Tumor Drug Sensitivity

Abstract: MicroRNAs play critical roles in regulating various physiological processes, including growth and development. Previous studies have shown that microRNA-124 (miR-124) participates not only in regulation of early neurogenesis but also in suppression of tumorigenesis. In the present study, we found that overexpression of miR-124 was associated with reduced DNA repair capacity in cultured cancer cells and increased sensitivity of cells to DNA-damaging anti-tumor drugs, specifically those that cause the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Moreover, miR-124 was found to be downregulated in gefitinib-resistant non-small cell lung cancer (NSCLC) cells, and overexpression of miR-124 sensitized gefitinib-resistant cells to gefitinib [34]. Also, miR-124 was found to be a potential therapeutic agent to improve the efficacy of chemotherapy with DNA-damaging agents in breast cancer [35]. Our study demonstrated that miR-124 expression was downregulated in DOX-resistant CRC tissues Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-124 was found to be downregulated in gefitinib-resistant non-small cell lung cancer (NSCLC) cells, and overexpression of miR-124 sensitized gefitinib-resistant cells to gefitinib [34]. Also, miR-124 was found to be a potential therapeutic agent to improve the efficacy of chemotherapy with DNA-damaging agents in breast cancer [35]. Our study demonstrated that miR-124 expression was downregulated in DOX-resistant CRC tissues Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that miRNAs are involved in the anti-cancer effects of many reagents [22]. MiR-21 is an oncogenic miRNA and is over-expressed in malignant glioma [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…www.microrna.org ) showed that multiple p53 or HIF-dependent miRs are predicted to bind to the ATMIN transcript, including miR-373 (a HIF-1α target) and miR-34 (a p53 target) 12 37 38 . In addition, a recent study, which screened for the miR-124 targets involved in the DNA damage response, found ATMIN to be regulated by miR-124 39 . Importantly, miR-124 is a known direct target of p53 suggesting that it is likely to be involved in down-regulation of ATMIN under hypoxia 40 .…”
Section: Discussionmentioning
confidence: 99%